2014
DOI: 10.1002/art.38867
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Antinuclear Antibodies and the HLA Class II Locus and Heterogeneous Characteristics of Staining Patterns: The Nagahama Study

Abstract: on behalf of the Nagahama Study GroupObjective. While antinuclear antibodies (ANAs) are observed in healthy populations as well as in patients with autoimmune diseases such as systemic lupus erythematosus (SLE), the detailed genetic background of ANAs has remained unclear. We undertook this study to identify the genetic determinants of ANAs in the general population in order to elucidate the underlying mechanisms of ANA production and to distinguish disease susceptibility genes from ANA production genes.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 39 publications
1
15
2
Order By: Relevance
“…In the majority of our cases (93%) the staining pattern was stable over time, but in four patients the pattern changed at least once. Nevertheless, the distribution herein was largely similar to that found in a previous Swedish SLE cohort, but with a higher observed proportion of H‐ANA‐positive individuals compared to both a large Japanese study with volunteers where S‐ANA constituted the dominating staining pattern and in a Mexican report which evaluated relatives of patients with autoimmune disease .…”
Section: Discussionsupporting
confidence: 85%
“…In the majority of our cases (93%) the staining pattern was stable over time, but in four patients the pattern changed at least once. Nevertheless, the distribution herein was largely similar to that found in a previous Swedish SLE cohort, but with a higher observed proportion of H‐ANA‐positive individuals compared to both a large Japanese study with volunteers where S‐ANA constituted the dominating staining pattern and in a Mexican report which evaluated relatives of patients with autoimmune disease .…”
Section: Discussionsupporting
confidence: 85%
“…While ANAs are observed in healthy populations as well as in patients with autoimmune diseases such as SLE, one genetic study was performed in Japanese participants that quantified ANA levels using indirect immunofluorescence to determine any correlation of ANA positivity with a genetic locus. The results showed that the nucleolar pattern showed different associations from other staining patterns, correlating with ANA positivity and with the HLA locus 8 . In this study, ANA positivity in Japanese volunteers ages range 30-75 years with low titres were found between 12.5 and 45.2%, and medium titres were found only 2.8%.…”
Section: Discussionmentioning
confidence: 86%
“…Titers above 1:40 were considered positive in the EAC. Titers above 1:80 were considered positive in the Nagahama study [28]. …”
Section: Methodsmentioning
confidence: 99%